(untitled) (Research, Society and Development, 2025)
The Escola da Terra Program is one of the National Rural Education Program (PRONACAMPO) actions. The program was launched by the Federal Government on March 20, 2012, through Ordinance No. 86 of February 2, 2013, and aims to promote an education that meets the reality of rural people and quilombolas. It supports access to and improvement of learning conditions, linking teaching work to the reality of the communities. It offers continuing education for teachers, focusing on methodologies appropriate to the subjects’ daily lives who vivify the school environment and the rural territory. Therefore, the tutoring provides additional support for the critical training of teachers, integrating theory and practice with social reality. Activities include school visits, board meetings, and educational workshops, intending to strengthen contextualized education and coexistence with the Semiarid region. We brought in Freire (1996), Martins (2006), Reis (2011), and Silva (2009) as theoretical intercessors to support this study. During the training process, it was observed that tutoring plays a fundamental role in consolidating the continued education of students in the academic environment.